Management of high-risk squamous cell carcinoma of the skin. Issue 5 (May 2011) - Samarasinghe, Venura; Madan, Vishal; Lear, John T
Cutaneous squamous cell cancer (SCC) is the second most common skin cancer, accounting for one-fifth of all cutaneous malignancies. The majority arise on the head and neck skin, and cumulative UV exposure is thought to be the most likely etiological factor. The majority of deaths from SCC occur in a high-risk subgroup of patients. This high-risk subgroup of patients can be identified as those with tumors greater than 2 cm in diameter; tumor thickness over 4 mm; moderately/poorly differentiated or desmoplastic histological SCC subtype; ear, lip, hand, feet or genital tumor site; presence of perineural or lymphovascular invasion; nodal metastasis at presentation; recurrent SCC; SCC arising from scars or chronic skin disease, for example, chronic ulcers; and SCC arising in immunosuppressed patients. It is important to identify and aggressively treat these patients, as high-risk SCC are associated with a greater mortality and morbidity. This article reviews the diagnosis and management of such high-risk SCC.